Microanalysis of oligodeoxynucleotides by cathodic stripping voltammetry at amalgam-alloy surfaces in the presence of copper ions - Hason, Stanislav; Vetterl, Vladimír (Talanta, 2006)
The application of gold amalgam-alloy electrode (AuAE) for a sensitive voltammetric detection of different oligodeoxynucleotides (ODNs) containing the purine units within the ODN-chains in the presence of copper is described. The detection of ODNs is based on the following procedure: (i) the first step includes an acidic hydrolysis of the ODN (ahODN) samples performing the release of the purine bases from ODN-chain; (ii) the second step includes an electrochemical accumulation of the complex of the purine base residues released from ODN-chain with copper ions Cu(I) (ahODN-Cu(I) complex) at the potential of reduction of copper ions Cu(II) on the amalgam-alloy electrode surfaces; (iii) finally followed the cathodic stripping of the electrochemically accumulated ahODN-Cu(I) complex from the electrode surface. The proposed electrochemical method was used for: (a) detection of different ODN lengths containing only adenine units (the number of adenine units within the ODN-chains was changed from 10 to 80), and (b) determination of the number of purine units within the 30-mer ODNs containing a random sequence segments involving both the purine and pyrimidine units. The intensity of the cathodic stripping current density peak (j(CSP)) of the electrochemically accumulated ahODN-Cu(I) complex increased linearly with the increasing number of purine units within the ODN-chains. We observed a good correlation between the percentage content of purine units to the whole length of different 30-mer ODNs and the percentage content of the intensity of the j(CSP) of the electrochemically accumulated 30-mer ahODN-Cu(I) complexes. The detection of acid hydrolysed 80-mer (A(80)) in the bulk solution and in a 20-mul volume is possible down to 200pM and 2nM at the AuAE, respectively. For the shortest 10-mer (A(10)) a detectable value of 5nM in the bulk solution on the AuAE was observed. The sensitive detection of different ODNs containing the purine units in their chains in the presence of copper can be also performed at the platinum amalgam-alloy (PtAE) and copper amalgam-alloy (CuAE) contrary to a lower sensitivity at the silver amalgam-alloy (AgAE) electrode.